answersLogoWhite

0


Best Answer

By following BODMAS, evaluate the inner brackets first, collecting terms together as you go:

B - 3(B - 4(1 - B)) = 54

→ B - 3(B - 4 + 4B) = 54

→ B -3(5B - 4) = 54

→ B - 15B + 12 = 54

→ -14B = 42

→ 14B = -42

→ B = -3

Check by substituting back into the original equation:

B - 3(B - 4(1 - B))

→ -3 - 3(-3 - 4(1 - -3))

→ -3 - 3(-3 - 4(4))

→ -3 - 3(-3 - 16)

→ -3 - 3(-19)

→ -3 + 57

→ 54 as required.

User Avatar

Wiki User

9y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: How do you solve this equation B-3(B-4(1-B)) equals 54?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions